1999
DOI: 10.1017/s0029665199001317
|View full text |Cite
|
Sign up to set email alerts
|

An overview of methods for assessment of free radical activity in biology

Abstract: fax +44 (0)151 706 5952, email mjj@liv.ac.ukAssays which purport to assess free radical activity in biological systems are multiple. However, despite numerous published descriptions of new methods and modifications of methods to assess free radical activity in biological materials, there is still a lack of reliable techniques for quantification of activity in vivo. Analysis of a number of related indicators and use of a variety of approaches appears the only reliable way to evaluate these processes in vivo. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 22 publications
(22 reference statements)
2
34
0
3
Order By: Relevance
“…Work from our laboratory has previously shown that patients with type 1 diabetes are susceptible to increased blood levels of free radicals as documented by EPR spectroscopy, the most direct method of measuring free radical species [27]. The present study has consistently confirmed this observation and in addition demonstrates that ascorbate prophylaxis attenuates exercise-induced oxidative stress.…”
Section: Discussionsupporting
confidence: 84%
“…Work from our laboratory has previously shown that patients with type 1 diabetes are susceptible to increased blood levels of free radicals as documented by EPR spectroscopy, the most direct method of measuring free radical species [27]. The present study has consistently confirmed this observation and in addition demonstrates that ascorbate prophylaxis attenuates exercise-induced oxidative stress.…”
Section: Discussionsupporting
confidence: 84%
“…MDA, a lipid peroxidation end product, is an indicator of oxidative stress (Jackson, 1999). In this study, the MDA levels of the brain were examined by spectrophotometric assay.…”
Section: L-nbp Decreased Oxidative Stress In 3xtg-ad Micementioning
confidence: 99%
“…É importante salientar que as substâncias produzidas pela peroxidação são instáveis e existe ausência de níveis detectáveis em alguns fluidos e tecidos (Jackson, 1999).…”
Section: Determinação Da Lipoperoxidação Pela Produção De Tbars Nos Tunclassified